50 THINGS TO THINK ABOUT AS AN EARLY CAREER RESEARCHER paving your way to success. - Robertson, Margaret J. (ROUTLEDGE, 2026)
This book for Early Career Researchers (ECRs) provides vital insights for jump-starting your research career and guidance on how you can find your own ways of knowing, being, doing, and communicating to progress your career.Charting a course through the first years of a research career, while retaining control of your life and your authenticity is more challenging than it has ever been. This book argues that there are multiple ways of being an ECR, and that research pathways are uniquely individual. It shows how to prepare yourself for your research journey and contains useful hints about preparing manuscripts, writing research grants, developing supervision skills, and forging a successful research career. Offering solutions to common challenges, it provides insights into preparing CVs, preparing for interviews and other opportunities for you and your career.Providing practical advice based on extensive experience, this book is essential reading for those completing, or who have recently completed, PhDs, as well as those in the early stages of their career in higher education.
Keywords: Research -- Vocational guidance.; elektronické knihy; electronic books